The Allures and Illusions of Modernity:Technology and Educational Reform in Egypt - Warschauer, Mark (Education Policy Analysis Archives, 2003)
Much of the research to date on educational technology has focused on its implementation in wealthy countries. Yet instructional technology has a special allure in the developing world, where it holds the promise not just of improving schools but also of hastening modernization. This article examines a national educational technology effort in Egypt, illuminating the contradictions between the rhetoric of reform and the reality of school practices. The analysis points to underlying political, cultural, and economic factors that constrain attempts to improve Egyptian schooling with technology.